Sarcoidosis associated massive pleural Effusion: Case report and literature review - Sergio David Angulo; Jessica Marcela Hermosa; Juan José Montoya; Isabel Cristina Sánchez; María Alejandra López; Marcela Patricia Orrego; Ángela María Martínez (Respiratory Medicine Case Reports)
Sarcoidosis is a systemic disease of unknown etiology, commonly involving the lungs. Pleural effusion is an uncommon initial manifestation. We present a case of massive recurrent pleural effusion refractory to corticosteroids, requiring surgical decortication and immunosuppressive therapy, with a favorable clinical outcome.